The burning heart - The Proterozoic geology and geological evolution of the west Musgrave Region, central Australia - Howard, H.; Smithies, R.; Kirkland, Chris; Kelsey, D.; Aitken, A.; Wingate, M.; Quentin de Gromard, R.; Spaggiari, C.; Maier, W. (Elsevier Inc., 2015)
The Musgrave Province is one of the most geodynamically significant of Australia's Proterozoic orogenic belts, lying at the intersection of the continent's three cratonic elements - the West, North and South Australian Cratons. While remoteness and cultural sensitivity have slowed geological research into this region, recent collaborative programs in Western Australia (the west Musgrave Province) have done much to address this. This Focus Review provides a synthesis of this, and previous, work investigating the Mesoproterozoic to Neoproterozoic geological evolution of the province. The Musgrave Province is a Mesoproterozoic to Neoproterozoic belt dominated by granites formed and deformed during several major events. A cryptic juvenile basement is exposed mainly in the east Musgrave Province as c. 1600-1550. Ma orthogneiss and in the west Musgrave Province as isolated outcrops of granulite-facies metagranites of the c. 1575. Ma Warlawurru Supersuite. Zircon Hf-isotopic data suggest an earlier major juvenile crust-forming event at c. 1950-1900. Ma. There is, however, no evidence that the province evolved over Archean crust. The c. 1600-1550. Ma period probably involved evolution within a primitive arc setting, perhaps developed on c. 1950-1900. Ma oceanic or oceanic-arc crust. Voluminous calc-alkaline plutonism was accompanied by clastic and volcaniclastic basin formation during the 1345-1293. Ma Mount West Orogeny. This stage traced the evolution of a continental arc reflecting the final amalgamation of the combined North and West Australian Craton with the South Australian Craton. The intervening c. 1400. Ma primitive crust - the Madura Province - on which the proto-Musgrave Province had evolved, was consumed during amalgamation. The thickened crust resulting from this accretion was drastically thinned at the beginning of the c. 1220-1150. Ma Musgrave Orogeny as this central part of the new combined craton entered an extraordinary period of high heat flow characterised by c. 100. m.y. of ultrahigh-temperature metamorphism and high-temperature, anhydrous, alkali-calcic magmatism sourced from MASH chambers developed at the base of the thinned crust. The ridged cratonic architecture and a massive accumulation of high radiogenic heat producing granites within the mid crust perpetuated a thin crustal regime. Voluminous magmatism was again triggered during the c. 1090-1040. Ma Giles Event with the evolution of the magmatism-dominated, Ngaanyatjarra Rift. This event was likely initiated through renewed movement along translithospheric faults that intersected the thermally perturbed Musgrave Province, pinned at a cratonic junction. Mantle-derived bimodal magmatism extended more or less continuously for 50. m.y., producing one of the world's largest layered mafic intrusions and supervolcano-sized additions of juvenile felsic crust, in the form of alkali-calcic to alkali, A-type, rhyolite deposits. Together, the Albany-Fraser Orogen, which developed over the southern margin of the West Australian Craton, and the Musgrave Province mark the preserved edge of the North and West Australian Craton. These two belts show remarkable chronological links between c. 1345 and 1150. Ma but contrasting histories before and after that period. Their period of shared evolution reflects collision and accretion of the South Australian Craton, but their tectonic setting and basement geology throughout that event were very different.